Psychological Impact among Frontline Police Personnel of Kathmandu Metropolitan City in Nepal: A cross-sectional Study - Devkota, Nishchal; Bam, Aayushi; Kumar Poudel, Ashok; Acharya, Surakshya; Karki, Rajesh; Luitel, Rashmi; Singh, Matrika (Annapurna Journal of Health Sciences, 2023)
Background: A job of police officer is such that they often have to undergo the mental anguish and pain internally. This study aimed to assess the psychological impact among frontline police personnel of Kathmandu Metropolitan City in Nepal. Methods: A cross-sectional study was conducted among randomly sampled frontline police personnel of Kathmandu Metropolitan City. A self-administered DASS questionnaire was used to assess the psychological impact. Total 373 sample was derived using the formula for proportion. A self-administered DASS questionnaire was used. Data were analyzed on SPSS 20. Results: The prevalence of depression was 67.8%, of these, majority (29%) of the frontline police personnel were moderately depressed, followed by mildly depressed (20.1%), severely depressed (11.3%), and extremely severely depressed (7.5%). Similarly, the prevalence of anxiety was 73.5%, given which mildly anxious (9.4%), and moderately anxious (32.4%), severely anxious (15%), and extremely severely anxious (16.6%). Likewise, that prevalence of stress was 23%, where the low proportion of them had mild stress (8.6%), stress (6.7%), severe stress (4.8%) and extremely severe stress (2.7). Conclusion: Due to their sensitive exposures and nature of work, front-line workers, such as police officers, have grown more prone to depression, anxiety, and stress. Given that policing is a physically, emotionally, and intellectually demanding profession, it is vital to equip officers with adequate psychological assistance.